Preliminary physiologically based pharmacokinetic modeling of renally cleared drugs in Chinese pregnant women. (9th July 2020) - Song, Ling; Yu, Zhiheng; Xu, Yifan; Li, Xiaobei; Liu, Xuanlin; Liu, Dongyang; Zhou, Tianyan
Abstract: Aim: The aim of this study was to build and verify a preliminary physiologically based pharmacokinetic (PBPK) model of Chinese pregnant women. The model was used to predict maternal pharmacokinetics (PK) of 6 predominantly renally cleared drugs. Method: Based on SimCYP Caucasian pregnancy population dataset, the preliminary Chinese pregnant population was built by updating several key parameters and equations according to physiological parameters of Chinese (or Japanese) pregnant women. Drug‐specific parameters of 6 renally cleared drugs were validated through PBPK modeling of Caucasian non‐pregnant, Caucasian pregnant and Chinese non‐pregnant population. The preliminary PBPK model of Chinese pregnant population was then developed by integrating the preliminary Chinese pregnant population and the drug‐specific parameters. This model was verified by comparing the predicted maternal PK of these 6 drugs with the observed in vivo data from the literature. Results: The preliminary Chinese pregnant population PBPK model successfully predicted the PK of 6 target drugs for different pregnancy stages. The predicted plasma concentrations time profiles fitted the observed data well, and most predicted PK parameters were within 2‐fold of observed data. Conclusions : The preliminary Chinese pregnant population PBPK model provided a useful tool to predict the maternal PK of 6 predominantly renally cleared drugs in Chinese pregnant women.